"God's Righteousness Is Revealed in Every Believer from Faith to Faithfulness" (Rom 1.17): A Possible Reading. Issue 1 (April 2021) - Lee, Yongbom
This study proposes understanding Rom 1.17 as: "For God's righteousness is revealed in every believer from faith to faithfulness, as it was written, 'The righteous will live by faith, '" based on various exegetical considerations in both its syntagmatic and literary context and its role in the overall shape of Romans. It highlights Paul's holistic and dynamic picture of Christian life in which justification by faith produces its fruits in a believer's everyday life.